2012
DOI: 10.1016/j.bpj.2011.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Lipid Bilayers under Tension

Abstract: Given the proposed importance of membrane tension in regulating cellular functions, we explore the effects of a finite surface tension on phase equilibrium using a molecular theory that captures the quantitative structure of the phase diagram of the tensionless DPPC/DOPC/Cholesterol lipid bilayer. We find that an increase in the surface tension decreases the temperature of the transition from liquid to gel in a pure DPPC system by ∼1.0 K/(mN/m), and decreases the liquid-disordered to liquid-ordered transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 17 publications
5
67
0
Order By: Relevance
“…Ursell et al (13) observed a repulsion of domains in deflated GUVs, caused by the induction of membrane curvature between the l o domains. In the case of PSMs, the rather large lateral membrane tension of about 1 mN·m −1 (23,24,32) prevents the induction of a 3D structure in the center of the PSM, although it does not significantly alter phase separation (33,34). This trait allows the l o domains to merge, leading to only one mobile domain in each PSM.…”
Section: Resultsmentioning
confidence: 99%
“…Ursell et al (13) observed a repulsion of domains in deflated GUVs, caused by the induction of membrane curvature between the l o domains. In the case of PSMs, the rather large lateral membrane tension of about 1 mN·m −1 (23,24,32) prevents the induction of a 3D structure in the center of the PSM, although it does not significantly alter phase separation (33,34). This trait allows the l o domains to merge, leading to only one mobile domain in each PSM.…”
Section: Resultsmentioning
confidence: 99%
“…Tension has also been hypothesized, but not confirmed, to influence the shapes of solid domains (25). Relevant to the current focus on the thermodynamic role of tension, tension was shown reduce the liquid-liquid coexistence temperature only slightly (a fraction of a Celsius degree for each 0.1 mN/m in tension) in cholesterol-containing phospholipid vesicles (26,27). …”
mentioning
confidence: 84%
“…The effect of surface pressure (or negative surface tension) is an effective increase in the melting transition temperature by a factor P Δ A melt /Δ H melt °, which will slow down the melting rate. 43 We can approximate a pressure-dependent melting rate by substituting T m from eq B1 with a pressure-dependent transition temperature T m ( P ): dAgeldt=CLbndtrue(TTnormalmtrue(1+PΔAmeltΔHmeltnormalotrue)true) The overall dynamics of melting will then depend on the balance of pressure building up through the area increase associated with melting and the rate of pressure relaxation through changes in vesicle shape and volume, which are implicitly included in the relaxation rate Γ, which would be expected to depend on pressure but may depend on the structural state of the vesicle as well. If we can treat surface relaxation as negligible on the melting time scale, (Γ = 0) then these two equations yield an exponential decay in the gel-phase area until the surface pressure effect on T m halts further melting: ΔAgel(t)Atot=ΔHnormaloχmeltκΔAtrue(TTnormalm(0)1true)true(1exptrue(CLbndAtotχmeltκΔAΔHnormaloTnormalm(0)ttrue)true)…”
mentioning
confidence: 99%